EVALUASI PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE MATERIAL REQUIREMENT PLANNING PADA HOME INDUSTRYSARANA BERSIH â€œLIMAâ€ - Pramono, Sugeng (Department of Management, 2014)
The purpose of this study is to determine the results of Raw Material Inventory Control evaluation with Material Requirement Planning method in May 2014, so the company Home Industry Sarana Bersih